(untitled) (International Journal on Stereo & Immersive Media, 2025)
In 2024, the 30th anniversary of Laurent Mannoni’s seminal work The Great Art of Light and Shadow: Archaeology of the Cinema was marked. Published in 1994 on the occasion of the centenary of cinema, the book is a cornerstone in the study of the origins of moving images, drawing on extensive archival research and an intimate understanding of cinematic technology. Mannoni’s approach resonates with the broader field of Media Archaeology as it explored the rich tapestry of innovation and experimentation that preceded the dominant narratives of cinema’s birth.